Stochastic modelling and availability analysis of repairable system of a milk processing plant. (3rd November 2021) - Kumar, Narendra; Tewari, P.C.; Sachdeva, Anish
This paper describes the performance evaluation of pasteurising system of a milk processing plant in terms of its operational availability. For the stochastic modelling and analysis Markov chains has been applied. Particle swarm optimisation (PSO) technique is implemented for optimising the results obtained. The optimum combinations of failure and repair rates for various subsystems can be useful in decision making such as maintenance priorities, spare parts and repairmen, etc. Based on this, a decision support system (DSS) has been developed which indicates the most critical components of the system that need the utmost care while setting maintenance priorities.